PROMOTING LEARNER INTEREST on ENGLISH WRITING THROUGH ENGLISH QUOTES - Nurul Hasanah Fajaria; Sixteen Amalia (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
As a foreign language, some students find difficulties to learn English at school. An attractive media such as English Quotes are expected to increase learners’ interest in English writing. Thirty participants who are active users of social media are asked to answer several question through questionnaire and interview. The result shown that English Quotes help the participants to learn English accidentally. Since they only read what are they interested in, they enjoyed the process and do not feel burden to do it. When they find unfamiliar words, they are pleased to search the meaning through both online and offline dictionary. As a result, it can increase their vocabulary. Last but not least, after they already understood of the meaning, they tried to rewrite and posted it in their social media status, thus it help them increase their interest in writing.